Instructors’ voice on giving students provisional grades: the case of a state university in Southern Philippines - Sheen Marie S. Puno; Arnel S. Travero; Jackielyn U. Abao; Ima Widyastuti; Rozanah Katrina Herda (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
During the course of the COVID-19 pandemic, universities and colleges opted to give students provisional (P) grades instead of directly failing the students who had not complied with academic requirements. This study presents the voices of the instructors of a University in Southern Philippines on giving students provisional grades. The participants of the study were the instructors from the three colleges of the University. The study was qualitative, and open-ended questions were used to gather data through interviews. Content analysis was used to analyze the data gathered. Themes generated from the participants include challenges in interacting with students, students’ lack of concentration, students’ lack of compliance, and students taking advantage of provisional grades. With this, the researchers recommend that the University should provide training and seminars to the instructors and students on topics such as mental health awareness, advocacy, and digital literacy. Moreover, whenever the University comes up with a new policy, it is beneficial to ask for feedback from stakeholders to gain insights into how the policy might affect them and ensure that their rights will be respected and upheld. This is to ensure that the policy is fair, transparent, and equitable